The socio-economic situation, food and nutrition insecurity in the Republic of Benin during the COVID-19 pandemic (Research, Society and Development, 2022)
Food and nutrition security is about promoting rights to access sufficient, quality food without compromising other essential needs. The measures of social distancing, the paralysis of non-essential economic activities imposed to control the pandemic of COVID-19 caused disruptions in food production and supply chains worldwide. The study aimed to assess the food and nutrition security status of households in the Republic of Benin and also the socioeconomic situation during the pandemic. The results showed that the COVID-19 pandemic increased the levels of poverty and food insecurity in Benin. Overall more than 50% of the participants were living on only one minimum wage or less and more than 50% were living in acute food insecurity including families with children. The central region of the country was the most affected by food insecurity followed by the northern region. There was a lack or low intervention of regional, economic and social policies to maintain jobs and guarantee food for the affected families. More governmental or non-governmental policies are needed to ensure food and nutritional security for low-income families.